A Study on Consumer Buying Behavior towards Foreign and Domestic Branded Apparels (Global Journal of Management and Business Research, 2018)
This study helps to inquest the factors which affect the buying behavior of consumers towards foreign and domestic branded apparels. The data was collected by distributing the globally accepted structured questionnaire among the respondents who are presently living in Dhaka Metropolitan city and regular buyers of apparels of different brands-foreign or local. Convenience sampling method was applied with a sample size of 200 consumers for data collection. Descriptive statistics were used to analyze the research objectives. The result of this study offers sagacity and evidence about the relationship between the components which impact consumer buying behavior for branded apparels. This study provides a clear understanding of each factor in the local consumer decision-making process for buying from any branded clothes. As the consumer has globally looked forward for using foreign branded clothes aside by domestic one, it now seems that the apparel manufacturers and marketers need to expand their own brands. Finally, it is settled in the this study that many factors are connected for buying apparels regarding brand performance, purchase intention, consumer's evaluation alongside consumer's demographic and economic factors.
Keywords: behavior; brand; factors; willingness; purchase intention